Donaciinae (Coleoptera: Chrysomelidae) of Turkey: species list and new records. Issue 3 (2nd July 2020) - Ekiz, Ali Nafiz; Geiser, Elisabeth; Gök, Ali; Kaya, Özgür Durmuş
Abstract: The Turkish Donaciinae are reviewed based on recently collected material, several museum collections, and the available literature data. In total, 21 species of Donaciinae are known from Turkey. Donacia aequidorsis Jacobson, 1894, D . polita Kunze, 1818, and Plateumaris rustica (Kunze, 1818 ) are reported for the first time for the Turkish reed beetle fauna. Local distributions are updated, and distribution maps are provided for 19 species of which exact localities are known.